Relationships between unilateral muscle strength qualities and change of direction in adolescent team-sport athletes - Thomas, C.; dos Santos, T.; Comfort, P.; Jones, P. A. (Sports, 2018)
Previous studies have reported an association between global measures of bilateral strength and change of direction (COD) ability. Yet, little is known about the association between unilateral muscle strength qualities and COD ability. The aim of this study was to explore the associations between unilateral muscle strength qualities and COD measures (COD speed (CODS) and COD deficit) when matched limb-for-limb (i.e., right limb vs. right limb, left limb vs. left limb) in adolescent team-sport athletes. One hundred and fifteen athletes (56 males, 59 females) active in cricket, netball, and basketball participated in this investigation. Each player performed trials of countermovement jump (CMJ), single-leg hop (SLH), isometric mid-thigh pull (IMTP) and eccentric knee extensor torque (ECC-EXT) to assess muscle strength qualities and 505 and modified 505 (505mod) to evaluate COD ability. Moderate-to-large correlations were observed between SLH and CODS (r = -0.43 to -0.67). Another important finding was that CMJ measures demonstrated moderate-to-large correlations with CODS (r = -0.38 to -0.69) and small-to-moderate correlations with COD deficit (r = -0.24 to -0.45). COD is underpinned by distinct muscle strength qualities and each contribute to specific phases of a COD task. It is therefore likely that such connections exist between muscle strength qualities and COD, with all qualities contributing to overall COD ability.